Determination of some components of citrus fruits wastes and monitoring bioactivities of these wastes in experimental animals - ابراهيم , مي; ديمة الدياب , (Latakia University Journal -Medical Sciences Series, 2023)
This research aims to identify the most important nutritional components in the albedo layer of Valencia (Citrus sinensis) fruit peel, and to evaluate the effect of albedo on weight and blood glucose values in experimental rats. The albedo layer was dried and ground into a fine powder, then the percentage of moisture, ash, fat, protein, carbohydrate, and dietary fibers were determined, and the levels of phenolic compounds were determined. The biological study was conducted on 18 female rats divided into two groups (n = 9). The first group was given high-fat diet (HFD), and the second group was given high-fat diet with albedo (HFD +A). The percentage of moisture, ash, fat, protein, carbohydrate and dietary fibers in albedo were (61.94, 3.57, 1.51, 3.19, 78.2, 13.45)%, respectively, and the content of phenolic compounds in albedo was 19.9 g GAE/kg. The addition of albedo to the diet led to a decrease in weight or to preventing its gain compared to the group that ate a diet without albedo in a statistically significant way (p<0.05), It also led to a significant decrease in blood glucose values in the mice of the second group compared to the first group (p<0.05).